Long leukocyte telomere length in prostate cancer patients at diagnosis is associated with poor metastasis-free and cancer-specific survival - Ulrika Svenson; Göran Roos; Pernilla Wikström (Tumor Biology)
Previous studies have suggested that leukocyte telomere length is associated with risk of developing prostate cancer. Investigations of leukocyte telomere length as a prognostic factor in prostate cancer are, however, lacking. In this study, leukocyte telomere length was investigated both as a risk marker, comparing control subjects and patient risk groups (based on serum levels of prostate-specific antigen, tumor differentiation, and tumor stage), and as a prognostic marker for metastasis-free and cancer-specific survival. Relative telomere length was measured by a well-established quantitative polymerase chain reaction method in 415 consecutively sampled individuals. Statistical evaluation included 162 control subjects without cancer development during follow-up and 110 untreated patients with newly diagnosed localized prostate cancer at the time of blood draw. Leukocyte telomere length did not differ significantly between control subjects and patients, or between patient risk groups. Interestingly, however, and in line with our previous results in breast and kidney cancer patients, relative telomere length at diagnosis was an independent prognostic factor. Patients with long leukocyte telomeres (⩾median) had a significantly worse prostate cancer–specific and metastasis-free survival compared to patients with short telomere length. In contrast, for patients who died of other causes than prostate cancer, long relative telomere length was not coupled to shorter survival time. To our knowledge, these results are novel and give further strength to our hypothesis that leukocyte telomere length might be used as a prognostic marker in malignancy.